Problèmes de l’agriculture marginale dans la zone pionnière de l’Est du Canada - Biays, Pierre (Cahiers de géographie du Québec)

(untitled) (Département de géographie de l'Université Laval, 1964)
A marginal farm can be defined by three criteria : the amount of improved land, the amount of time spent by the operator off the farm, and the absolute and relative income derived from agriculture.Both human and physical factors explain the deficiencies of marginal agriculture in the study area. The settlers' lack of agricultural experience, improper agricultural specializations, and the small size of the parcels of improved land (and consequently of the cattle herds) are the important human factors. The main physical limitations are climatic (especially the cool summer temperatures and the short length of the frost-free period), and pedologic.More research is needed before political decisions can be made concerning the future of these areas of marginal agriculture. Surveys of the marginal farms and studies of the physical limitations to agriculture should be made not only by economists and pedologists, but also by geographers.